1988
DOI: 10.1093/oxfordjournals.jbchem.a122245
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental Sialidase: Further Purification and Characterization

Abstract: An acid sialidase [EC 3.2.1.18] has been purified from human placenta by means of successive procedures including extraction, Con A-Sepharose adsorption, ammonium sulfate precipitation, activation, p-aminophenyl thio-beta-D-galactoside-CH-Sepharose (PATG-Sepharose) affinity chromatography and high-performance liquid chromatography on a Shim pack Diol 300 column. The purified enzyme liberated sialic acid residues from sialooligosaccharides, sialoglycoproteins, and gangliosides. In particular, gangliosides GM3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Few reports on human lysosomal neuraminidase have been published, because the enzyme has low stability during purification and requires PPCA for the expression of its activity (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports on human lysosomal neuraminidase have been published, because the enzyme has low stability during purification and requires PPCA for the expression of its activity (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1. 18) is an acid glycosidase that catalyzes the removal of the terminal sialic acid residues of glycoconjugates (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Mammalian lysosomal neuraminidase is associated with protective protein/cathepsin A (PPCA; EC 3.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioside GM1 13-galactosidase assays were carried out as described (20) using human liver 3-galactosidase purified to near homogeneity (21) as the enzyme source. A partially purified preparation of human placental sialidase prepared as described by Hiraiwa et al (22) was used as the source of sialidase. Sialidase assays were carried out as described (22) using gangliosides GM3 and GD1a as substrates, measuring released sialic acid by a sensitive fluorescence assay (23).…”
Section: Methodsmentioning
confidence: 99%
“…The molecular mechanism of sialidase deficiency in galactosialidosis has never been characterized since until recently the lysosomal sialidase has not been cloned or purified. The sialidase activity has always been associated with the 1n27 MDa complex in the process of purification from tissues [16][17][18][19][20]. The dissociation of the complex resulted in the complete inactivation of sialidase.…”
Section: Introductionmentioning
confidence: 99%